Plasma triacylglycerol extraction in human adipose tissue in vivo: effects of glucose ingestion and insulin infusion. - Coppack, S; Frayn, K; Humphreys, S (1989)
Extraction of endogenous triacylglycerol (TAG) was measured across the subcutaneous adipose tissue of the abdominal wall and across forearm muscle in 16 studies on 13 normal subjects. After overnight fast there was significant TAG extraction across both adipose tissue (4 per cent) and muscle (1 per cent). After 75 g oral glucose (8 subjects), there was a rise in the arterial TAG concentration to a peak at 60 min, with a concomitant increase in extraction across adipose tissue (to 9 per cent). During insulin infusion (8 subjects; plateau insulin concentration 50-55 mU/l) with the plasma glucose 'clamped' at the fasting level, arterial TAG levels fell steadily, and extraction across adipose tissue and muscle decreased. The ability to measure triacylglycerol extraction by adipose tissue in vivo opens up many possibilities for metabolic and nutritional studies.